Early Detection of High-Risk Pregnancy Through 14T Antenatal Care Examination at the North Ponorogo Health Center - Rumpiati; Diah Septi Anggraini; Rini Dwi Astuti (Universitas STRADA Indonesia, 2026)
High-risk pregnancy remains one of the major contributors to maternal and neonatal morbidity and mortality. Early detection through comprehensive antenatal care (ANC) services is essential to prevent pregnancy complications. One of the integrated antenatal service standards implemented in Indonesia is the 14T antenatal examination, which includes physical assessment, laboratory examination, preventive interventions, and health education for pregnant women. This community engagement activity aimed to detect high-risk pregnancies early through the implementation of the 14T antenatal examination and to improve pregnant women’s knowledge regarding the importance of routine antenatal care. The activity was conducted in February 2023 at the North Ponorogo Health Center involving 15 pregnant women who attended antenatal visits. The implementation consisted of pregnancy examinations based on the 14T standard and health education regarding pregnancy care and danger signs during pregnancy. Knowledge assessment was conducted using a questionnaire before and after the educational intervention. The results showed that most pregnant women had normal pregnancy conditions; however, several risk factors were identified, including low hemoglobin levels, elevated blood pressure, and poor nutritional status based on mid-upper arm circumference measurements. Evaluation results indicated an increase in pregnant women’s knowledge after the education session. The proportion of participants with good knowledge increased from 20% before education to 73.3% after education. These findings indicate that the 14T antenatal care examination combined with health education effectively supports early detection of high-risk pregnancies and improves pregnant women’s awareness regarding the importance of routine antenatal care to maintain maternal and fetal health.